2020
DOI: 10.1137/19m1275334
|View full text |Cite
|
Sign up to set email alerts
|

An Approximation of Theta Functions with Applications to Communications

Abstract: Computing the theta series of an arbitrary lattice, and more specifically a related quantity known as the flatness factor, has been recently shown to be important for lattice code design in various wireless communication setups. However, the theta series is in general not known in closed form, excluding a small set of very special lattices. In this article, motivated by the practical applications as well as the mathematical problem itself, a simple approximation of the theta series of a lattice is derived. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In [13], it was shown that well-rounded lattices yield promising candidates for lattice codes in wireless communications [26] and physical layer security [6]. In [2] a means to approximate theta functions was given, enabling efficient comparison of candidate lattice codes. It was also noted in [13] that the densest packings might not provide the best candidates due to their large kissing numbers, and hence a study on generic well-rounded lattices having minimal kissing numbers was proposed.…”
mentioning
confidence: 99%
“…In [13], it was shown that well-rounded lattices yield promising candidates for lattice codes in wireless communications [26] and physical layer security [6]. In [2] a means to approximate theta functions was given, enabling efficient comparison of candidate lattice codes. It was also noted in [13] that the densest packings might not provide the best candidates due to their large kissing numbers, and hence a study on generic well-rounded lattices having minimal kissing numbers was proposed.…”
mentioning
confidence: 99%